SKI AREAS AND SLOPES IN ROMANIA. REVIEWING CURRENT STATE OF WINTER SPORTS TOURISM UNFOLDING POSSIBILITIES WITHIN CARPATHIAN MOUNTAINS - N. CIANGĂ; Bianca Sorina RĂCĂŞAN (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
Ski Areas and Slopes in Romania. Reviewing Current State of Winter Sports Tourism Unfolding Possibilities within Carpathian Mountains. This study is reviewing nowadays Romania’s tourism supply (2015) – laying special emphasis on the North-West Development Region’s situation – in terms of winter sports potential (resources) and material and technical base (specific infrastructure). It calls into question a highly discussed topic within the domain of interest of Tourism Geography, whose recursiveness could be justified by countinuous changes that influence the quantitative and qualitative configuration of ski areas, ski tracks and related equipment.